Free for Mission: Missional Church and Ethnographic Fieldwork - Hagley, Scott J. (Ecclesial Futures, 2020)
Working at the intersection of ethnographic and missional theology, this essay argues for the central role of fieldwork for discerning missional identity in congregations. Recent developments in ecclesiology and ethnography have clarified the embodied nature of theological knowledge, disclosing the practical wisdom and cultural locatedness of the researcher and congregation. While ethnography has been used to help congregations understand their context and discern a missional vocation, the ongoing theological and formational nature of such practices are often undertheorized in relationship to missional church. Drawing from Robert Jenson’s notion of the Spirit as God’s freedom, liberating God and creature for God’s future, this essay suggests ethnographic fieldwork as a liberative practice for the congregation, freeing it to participate in the boundary-crossing and sensemaking work of missional church. In working with congregations, I’m often greeted by some version of the question: “Are we (meaning, the congregation I’m working with) missional yet?” The question comes loaded with curiosity and concern. What, they ask, is a missional church, and would we know one if we saw it? Even more significant: how will we know when the work we are doing to renew our theological imagination and develop partnerships with our neighbors will pay off? The question comes from a good place, but it also leads into a deceptive trap, for any answer will betray the dynamism that “missional” tries to name (Guder 1998, 3–5). And yet, the question also unveils a theo-practical ambiguity at the heart of the missional church. The problem is not just that missio Dei theology holds together unreconciled tensions between the God-church-world relationship, but that the boundary-crossing practices that shape the missional vocation of a congregation are viewed instrumentally, as a means to a missional end. Congregations, seeking to identify as “missionary by [their] very nature,” and reorient congregational life through practices of missional discernment, can be forgiven for thinking of “missional” as a fixed arrival point (Guder 2015, 9). In what follows, I explore the theological significance of ethnographic practices for missional congregations. A staple of many approaches to missional renewal and missional church plants, church leaders and steering committees regularly employ the basic tools of ethnographic fieldwork to better understand their own community and their context or neighborhood (Croft and Hopkins 2015; Roxburgh 2011). In descriptive terms, these practices equip congregants for deep listening, attentive observation, and disciplined curiosity. They also place congregants in new places and with new people, drawing these experiences into congregational reflection and discernment. While neither professional ethnographers nor academic theologians, congregants are given through these practices new connections to neighbors and offered new vantage points from which to reflect upon the life and ministry of the congregation. As such, they are not simply a means to a missional end, but rather practices that already participate in God’s missional future. Congregational ethnographic fieldwork can cultivate new social realities which glimpse—and perhaps even liberate—the congregation for God’s mission in its particular context. Of course, ethnographic fieldwork is not a theological practice by itself, nor can missional theology be collapsed into ethnography. At stake in this discussion is how otherness is reconciled with the missio Dei, how one envisions the relationship between God and God’s creation, the church and God’s present and coming Reign (see Swart et al. 2009). Drawing from Robert Jenson’s understanding of the Spirit as God’s freedom and God’s future, I suggest a liberative approach to missional church. Rather than a fixed identity or a future telos, the missional church is liberated for God’s mission by and through the neighbor, the stranger, the other in and through the ministry of the Holy Spirit. The church sent into the world recognizes and receives God’s “preferred and promised future” in the concrete relationships cultivated (Keifert 2006, 16). Ethnography, shaped by this missional intention, becomes an ongoing practice for missional theology, not only a step toward a missional identity.